Elaboration of a Frame Model for Intensification and Managing Requirements to Learning Outcomes in Regional Systems of Continuing Professional Education - Ovchinnikova, Iraida G.; Kurzaeva, Lubov V.; Solomatina, Tamara B.; Chusavitina, Galina N.; Petelyak, Vladimir E.; Zerkina, Natalya N.; Lomakina, Yekaterina A.; Musiychuk, Maria V. (International Review of Management and Marketing, 2016)
The relevance of the declared in the article problem is caused by both universal integration processes and necessity of elaboration of effective management mechanisms for requirements to learning outcomes .First of all the qualifications frameworks of any level is created for formation of the interaction basis between the labor market and the system of education through establishment of compliance to qualification requirements of knowledge, abilities and competences regardless of a form of their acquisition (formal, informal, non-formal). The aim of the research is a qualifications framework elaboration of regional system of continuing professional education as a model of identification and adaptive management of requirements to personality’s educational outcomes. The article focuses on elaboration of the qualifications framework for system of continuing professional education in Chelyabinsk region. The research is based on methods of the system analysis and the competence-based approach is applied. The work presents the elaborated regional qualifications framework for system of continuing professional education, on the example of the Ural region: requirements to the contents, structure and structure concerning system of descriptors, qualification levels; the scheme of coordination of the developed qualifications framework with the project of the National qualifications framework of the Russian Federation; the ways of achieving qualification levels according to respondents’ opinions who are representatives of educational community and labor market. The results of the research can be the basis for creating an adaptive control system of requirements to the results of training in a regional education system and also they can be used for elaboration of adequate requirements for labor market, educational community, systems of certification of graduates of professional education establishment and certification of employees of the enterprises. Keywords: Qualifications Framework, Competence-Based Approach, Formal Training, Informal Training, Non-Formal Training, Adaptive Management of Education. JEL Classifications: A23, I23, I26